PENGAWASAN ASURANSI DIGITAL UNTUK KEAMANAN DATA NASABAH OLEH OTORITAS JASA KEUANGAN - Adani, Sajida; Ratnawati, Elfrida; Rahmawan, Dhany; Indirahati, Novina Sri; Bustani, Simona (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Digital insurance is a product developed by insurance companies by following current technological developments. Supervision of personal data in digital insurance is carried out by insurance companies, while the Financial Services Authority (OJK) only supervises the insurance company's business activities. The problem in this writing is whether digital supervision is really needed for the security of customer data by the OJK? The results of the discussion are that it is true that supervision of customer data is needed by the OJK because currently supervision of digital insurance customer data is only carried out by insurance companies and it is very vulnerable to leaks of personal data, so OJK's authority is needed to carry out digital supervision on personal data managed by insurance companies. the. Therefore, a legal umbrella is needed for the OJK to carry out digital supervision of personal data.Keywords: Digital Insurance, Supervision, Insurance Company, Financial Services Authority